2001
DOI: 10.1046/j.1365-2133.2001.04288.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and association of HLA class II genes with vitiligo in a Dutch population

Abstract: Both DRB4*0101 and DQB1*0303 alleles provide significant susceptibility for vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 17 publications
(26 reference statements)
5
77
1
1
Order By: Relevance
“…The study of major histocompatibility complex genes has revealed associations of vitiligo with certain human leukocyte antigens. 16,17 Polymorphic markers in the CTLA-4 gene that are associated with autoimmunity are also associated with vitiligo that occurs with other autoimmune disorders. [10][11][12] Vitiligo can also develop as 36 Likewise, the autoimmune susceptibility loci AIS1, AIS2 and SLEV1 are associated with generalised vitiligo that occurs with other autoimmune conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of major histocompatibility complex genes has revealed associations of vitiligo with certain human leukocyte antigens. 16,17 Polymorphic markers in the CTLA-4 gene that are associated with autoimmunity are also associated with vitiligo that occurs with other autoimmune disorders. [10][11][12] Vitiligo can also develop as 36 Likewise, the autoimmune susceptibility loci AIS1, AIS2 and SLEV1 are associated with generalised vitiligo that occurs with other autoimmune conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Furthermore, several genes that have a role in regulating immunity have been associated with susceptibility to vitiligo including: polymorphic markers in the cytotoxic T lymphocyte antigen-4 (CTLA-4) gene, the autoimmune susceptibility loci AIS1, AIS2, AIS3 and SLEV1 and certain human leukocyte antigen specificities of the major histocompatibility complex. [10][11][12][13][14][15][16][17] Recently, the missense R620W polymorphism in the PTPN22 gene at nucleotide 1858 (1858C-T) in codon 620 (620Arg-Trp) has been associated with autoimmune diseases including type I diabetes mellitus, Graves' disease, systemic lupus erythematosus and rheumatoid arthritis. [18][19][20][21][22][23][24][25] The gene, located on chromosome 1p13, 19 encodes lymphoid protein tyrosine phosphatase (LYP), which is important in the negative control of T lymphocyte activation.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier start of vitiligo (up to 7 years) was found in children with vitiligo and a positive family history of vitiligo (17). Th ere is clear evidence of the association of certain MHC haplotypes with a positive family history of vitiligo, onset timing, severity of disease and ethnic origin (15,16). As a possible theory for the etiology of vitiligo the following are cited: the autoimmune, oxidative stress theory (theory of self-destruction of melanocytes) and the neurogenic theory (1,2,3,4).…”
Section: Th E Etiology and Pathogenesis Of Vitiligomentioning
confidence: 85%
“…In patients with early onset of vitiligo (before age 30), vitiligo is caused by the dominant mode of inheritance with incomplete penetration. However, in patients with late onset (aft er age 30), predisposition to vitiligo is the result of a recessive genotype and the infl uence of the external environment (15,16). An earlier start of vitiligo (up to 7 years) was found in children with vitiligo and a positive family history of vitiligo (17).…”
Section: Th E Etiology and Pathogenesis Of Vitiligomentioning
confidence: 99%
“…21 Zamani et al reported an increased frequency of HLA-DRB4*0101 and -DQB1*0303 alleles in the Dutch population. 22 In black patients there was a higher frequency of HLA-DR4 and -DQw3 antigens. 23 In Turkey, HLA-DRB1*03, -DRB1*04 and -DRB1*07 alleles were considered risk markers.…”
Section: Vitiligomentioning
confidence: 99%